Pengaruh Ketebalan Lapisan Tipis ZnO terhadap Kinerja Sel Surya Perovskit Fleksibel - Ekarani, Putri; Prima, Eka Cahya; Rusdiana, Dadi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2023)
Photoelectrode preparation that requires high heating temperatures will hinder the future development of PSCs on flexible plastic substrates. Therefore, ZnO is a viable alternative for flexible PSCs because it can be processed at low temperatures. This research focuses on the influence of ZnO photoelectrode layer thickness on the optical properties and performance of PSCs. The transmittance of ZnO thin films was found to be more than 50% in each sample. In addition, the bandgap obtained ranged from 3.12 to 3.20 eV. The efficiency results are 0.90×10-5% at a thickness of 10 µm, 1.09×10-5% at a thickness of 8 µm, 2.68×10-5% at a thickness of 6 µm, and the best efficiency is 4.31×10-5% at 4 µm thickness. Based on the results of research that has been carried out, reducing the thickness of the ZnO photoelectrode layer can increase the transmittance and efficiency of solar cells so that solar cell performance increases.